2013
DOI: 10.1016/j.vaccine.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Incremental cost-effectiveness evaluation of vaccinating girls against cervical cancer pre- and post-sexual debut in Belgium

Abstract: Extending HPV vaccination to females post-sexual debut could lead to a substantial reduction in CC-related burden and would be cost-effective in Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The discount rates for cost-effectiveness studies in the Netherlands are 4 and 1.5% for cost and health outcomes [28,29,62,63], respectively. Only few countries/studies implement a different discounting for costeffectiveness, for example, only studies performed in Taiwan [55] and Belgium [64] implemented a 3% annual discount rate for cost and 1.5% for utility. These studies were unique since most countries [65][66][67] implementd equal discount rates for both parameters in their economic studies.…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…The discount rates for cost-effectiveness studies in the Netherlands are 4 and 1.5% for cost and health outcomes [28,29,62,63], respectively. Only few countries/studies implement a different discounting for costeffectiveness, for example, only studies performed in Taiwan [55] and Belgium [64] implemented a 3% annual discount rate for cost and 1.5% for utility. These studies were unique since most countries [65][66][67] implementd equal discount rates for both parameters in their economic studies.…”
Section: Discussion and Limitationmentioning
confidence: 99%
“…Default values of quality of life weight at different health states are based on published literature, and the population at different health states is based on the Markov disease progress/regression model (Fig. 10) [20][21][22].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of course, some studies about HPV vaccination of targeted groups have demonstrated economic value (Aponte-Gonzalez et al, 2013;Demarteau et al, 2013;Drolet et al, 2013;Elbasha et al, 2009;English et al, 2013;Fesenfeld et al, 2013;Kim et al, 2007;Natunen et al, 2013;Turner et al, 2013;Woertman and van der Wilt, 2013). However, the present study also considered the home environment when defining the socially vulnerable group.…”
Section: Discussionmentioning
confidence: 88%